2018
DOI: 10.1111/ffe.12839
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial ratcheting behavior and fatigue life models of commercial pure titanium

Abstract: The uniaxial fatigue and ratcheting behavior of commercial pure titanium (CP‐Ti) was investigated by asymmetric cyclic stress‐controlled experiments at room temperature. The effects of mean stress, stress amplitude, stress ratio, and peak stress on ratcheting behavior and fatigue life were discussed. It was found that increasing mean stress, stress amplitude, and peak stress or decreasing stress ratio reduced fatigue life and promoted ratcheting behavior. The applicability of different fatigue life models was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
(149 reference statements)
0
12
0
Order By: Relevance
“…This means that the average tensile stress present in the test load will result in the accumulation of strain in the tensile direction. 16,29 In order to analyze the ratcheting strain evolution, Figure 5A shows the variation of ratcheting strain in the X-direction and Y-direction with the number of cycles for different load ratios. The ratcheting strain for biaxial loading conditions is defined as follows: 7,16,30 where ε max and ε min represent the maximum strain and minimum strain in the cyclic period.…”
Section: The Influence Of Load Ratio and Phase Shift On Ratcheting Ef...mentioning
confidence: 99%
See 3 more Smart Citations
“…This means that the average tensile stress present in the test load will result in the accumulation of strain in the tensile direction. 16,29 In order to analyze the ratcheting strain evolution, Figure 5A shows the variation of ratcheting strain in the X-direction and Y-direction with the number of cycles for different load ratios. The ratcheting strain for biaxial loading conditions is defined as follows: 7,16,30 where ε max and ε min represent the maximum strain and minimum strain in the cyclic period.…”
Section: The Influence Of Load Ratio and Phase Shift On Ratcheting Ef...mentioning
confidence: 99%
“…Furthermore, the use of DIC also helps to provide a step-bystep understanding of crack emergence and extension. 16 The left-hand portion of Figure 8 shows the actual camera record of crack initiation. It can be seen that all crack initiation occurs in the central area of the specimen.…”
Section: Effect Of Different Loading Paths On Initial Crack Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of ratcheting severely influences the fatigue life of engineering components, especially for structures subjected to low cycle fatigue . Experimental studies on cyclic‐plastic behaviour of ferrous and non‐ferrous materials by numerous investigators have revealed the influence of mean stress, stress amplitude, and nature of loading on ratcheting behaviour of materials, and there exists several reports on modelling the cyclic‐plastic behaviour of materials. The existing constitutive models are popularly focused towards predicting the ratcheting behaviour of ferrous materials.…”
Section: Introductionmentioning
confidence: 99%